New record of arbuscular mycorrhizal fungi in Nothoceros fuegiensis (Dendrocerotaceae, Anthocerotophyta) - Cottet, Agustina Celeste; Messuti, María Inés (Instituto de Ecología, A.C., 2020)
Background and Aims: Arbuscular Mycorrhizal Fungi (AMF) are associated, in nature, with several species of hornworts (Anthocerotophyta). The aim of this study is to describe and characterize for the first time AMF colonization in Nothoceros fuegiensis (Dendrocerotaceae).Methods: The material examined was collected in cold temperate forest dominated by Nothofagus spp. The plants were conditioned, stained and analyzed according to specific techniques for bryophytes.Key results: The mycorrhizal association in N. fuegiensis is described for the first time. A brief description and illustration of the plant and the characteristic structures of the mycorrhizal fungus are presented. The percentage of colonization ranges from 9-40%, occasionally absent and its morphological type is Paris.Conclusions: The association between AMF and a hornwort, N. fuegiensis, is described, thus providing new information on the records of this type of association present in different bryophyte taxa in little-known or unexplored environments.